Determinants on student’s loan default: a study in Menara Maybank / Norellani Sukri - Sukri, Norellani (Faculty of Business and Management, 2015)
Education loan default is increasing by time in worldwide. Many students tend to borrow to pursue their studies in higher level of education. The higher the education level, the higher the amount of loan borrowed. According to Shafinar Ismail (2011), itis almost 50% cases of default rate of education loan in Malaysia. It portrayed that some graduates take no action in order to pay back their education loan. In this research, some variables will be test to determine the most determinants that affect the student loan default in Malaysia. The findings are of great relevance to the federal government that act as the fund agencies, to plan better for the loan advancement and recovery process once they really understand the main reason of default among students. The increase in recovery rate will bring in funds that can be lent to other new borrowers or used for strengthening the educational infrastructure (Shafinar Ismail,2011).